2004
DOI: 10.1002/jbm.a.30108
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic mechanical strain alters tissue‐factor activity in rat osteosarcoma cells cultured on a titanium substrate

Abstract: Tissue factor (TF), a transmembrane glycoprotein, plays a role in the initiation of blood coagulation at sites of vascular injury. Activated products of coagulation may then enhance inflammatory responses. The present investigation assesses the ability of rat osteosarcoma (UMR-106) cells cultured on titanium alloy (Ti6Al4V) to express differential surface TF activity in response to cyclic mechanical strain. Strains ranged from -2000 micro-strain to +2000 micro-strain, and durations from 5, 10, and 20 min per d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…SAOS-2 cells were assessed using atomic force microscopy, confocal microscopy, and cell-based assays. As cyclic mechanical strain has been reported to affect osteosarcoma cell biology depending on the frequency by which the stretch is applied to cells [38], we started the investigation by screening the best frequency capable of inducing the widest biological response. Our results demonstrated that a 1 Hz frequency of mild mechanical stretching (corresponding to 0.5% Ɛ elongation) applied for 3 days was able to increase the proliferation rate (Supplementary Figure S1A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAOS-2 cells were assessed using atomic force microscopy, confocal microscopy, and cell-based assays. As cyclic mechanical strain has been reported to affect osteosarcoma cell biology depending on the frequency by which the stretch is applied to cells [38], we started the investigation by screening the best frequency capable of inducing the widest biological response. Our results demonstrated that a 1 Hz frequency of mild mechanical stretching (corresponding to 0.5% Ɛ elongation) applied for 3 days was able to increase the proliferation rate (Supplementary Figure S1A).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical stresses from the microenvironment have been reported to regulate the PI3K/Akt signaling pathway (the most activated downstream effectors in the oncogenic landscape), promoting the expression of MMP-2 and MMP-9, thus degrading ECM and enabling osteosarcoma cell invasion and metastasis [29][30][31]. Several MMPs have been associated with mature invadopodia [38], including MMP-2, which was found to have an upregulated expression following mechanical stimulation [44].…”
Section: Discussionmentioning
confidence: 99%